Apakah Pandemi Covid-19 Mempengaruhi Kualitas Pendapatan? - Tenripada Tenripada; Arung Gihna Mayapada; Muhammad Afdhal; Andi Ainil Mufidah Tanra; Husnul Hatimah; Muhammad Ilham Pakawaru; Indra Basir; Septian Septian (Jurnal Akuntansi dan Pajak, 2022)
This study aims to empirically examine the impact of the COVID-19 pandemic on the quality of earnings reported by companies in the restaurant, hotel, and tourism sub-sector in Indonesia. This research is quantitative research with the data analysis technique of paired sample t-test. The research period is before and during the COVID-19 pandemic, namely 2019-2020. Earnings quality in this study is operationalized by discretionary accruals calculated using the model of Kothari et al. (2015). This study reveals no significant difference in earnings quality between before and during the COVID-19 pandemic. However, the mean earnings quality before the Covid-19 pandemic was higher than during the Covid-19 pandemic. This research contributes to providing empirical evidence on earnings quality during crises such as the COVID-19 pandemic. The results of this study also contribute practically to regulators in formulating policies related to financial statements during situations.